CP-019 Risk factors for anaemia development during therapy with ribavirin plus direct acting antivirals. (25th February 2017) - Molina, E; Nieto, P; Cañizares, S; Franco, B; Tauste, B; Sierra, F
Abstract : Background: Anaemia is a common adverse event associated with ribavirin therapy in hepatitis C patients. Peginterferon/ribavirin was the cornerstone of treatment of hepatitis C virus (HCV) patients until 2011. Purpose: To assess the incidence of anaemia and the risk factors predictive of anaemia in the context of ribavirin plus new direct acting antiviral (DAA) agents. Material and methods: A 1 year retrospective study was performed during 2015. Anaemia was defined as a single occurrence of haemoglobin <10g/dL at any point during treatment. Serum haemoglobin assessments were obtained at baseline and at weeks 0, 4, 8, 12, 16, 20 and 24. Pretreatment factors with potential to act as prognostic indicators of anaemia including age, sex, type of treatment, genotype, FibroScan score, cirrhotic yes/no, HCV RNA titre, dose 1000 mg/1200 mg, glomerular filtration rate, alanine transaminase, albumin, treatment duration 12 vs >12 weeks and baseline haemoglobin, and on-treatment factor as week 2 change from baseline, were analysed by univariate and multivariate logistic regression analyses. Results: 152 patients were analysed, 78.30% men, mean age 54.73 years (95% CI 53.35–56.11), CKD-EPI 98.00 mL/min (93.17–98.55). Genotypes frequencies were: g1 (67.10%), g2 (3.30%), g3 (15.80%) and g4 (13.30%). 62.50% of patients were cirrhotic and 84.20% were treated for 12 weeks. 23 (15.10%) had anaemia. The largest decrease in haemoglobin levels was the change from baseline to week 4. The slope continued almost flat thereafter. The mean decrease in haemoglobin during treatment was 2.67 g/dL (2.45–2.90). Multivariate analysis revealed that glomerular filtration rate, baseline haemoglobin, treatment duration >12 weeks and estimated week 2 change from baseline were significantly associated with the likelihood of developing anaemia (p <0.05). As a consequence, two models were developed to predict patients at risk of anaemia: the pretreatment model, using the first three variables, with a positive predictive value (PPV) of 86.60%, and the on-treatment model, adding the fourth variable, with a PPV of 95.00%. Conclusion: The incidence of anaemia with DAA has been less than that with peginterferon combinations. Glomerular filtration rate, baseline haemoglobin, treatment duration >12 weeks and estimated week 2 change from baseline were demonstrated to predict the risk of anaemia. References and/or acknowledgements: We thank Torrecardenas´s hospital pharmacists for their support. No conflict of interest